DEVELOPMENT OF COUNSELING GUIDANCE PROGRAMS IN ELEMENTARY SCHOOLS (SD) - Devi Sakinah Nasution; Neviyarni; Firman (Literasi Nusantara, 2022)
In elementary schools, counseling services are needed in helping students so that they are able to solve problems and develop their potential. In addition, BK teachers also help classroom teachers to provide guidance and services to elementary school students, so that guidance and counseling services can be maximized. For this reason, the development of BK programs in schools is the basis of the implementation and BK services carried out by BK teachers, for that a program must be made well and adapted to the needs of students (nedd asssment). The program that is designed must be in accordance with the stages of BK program design in schools will have a positive effect on students later both in terms of learning outcomes and in terms of social.